Valuing cultural heritage benefits to urban and regional development - Patrizia Riganti; Peter Nijkamp (European Regional Science Association (ERSA), 2004)
This paper discusses the role that cultural heritage has in shaping social capital in contemporary cities, and the available valuation methodologies capable of measuring its impacts on cities' economic growth. First, the economic nature of cultural goods and the role played by their valuation in regional planning is discussed. Then a critical review of the current available valuation methodologies is presented. Finally, the potential of meta-analysis is debated. Cultural heritage represents the record of mankind achievements and relationships with the world. Therefore, it has always a local dimension, though sometimes it embeds universally shared values. The concept of heritage is not given, but created by a community, by people who attach values to some objects, rites, languages, contexts, lifestyles, historic sites and monumental buildings. Labelling something as heritage represents a value judgment, which distinguishes that particular object from others, adding new meaning to it. Cultural heritage summarises people's identities, shapes communities' ones, and to this extent contributes to the creation of social capital. Heritage is a social, economic, and cultural resource. Heritage valuation becomes a tool to better understand the significance of heritage to different sections of society. The valuation process aims to assess existing values as attached by the relevant population. However, the ultimate aim in the context of policy analysis is to value in order to achieve the valorisation of our heritage, in order words, to add new values to the existing ones. Therefore, valuation represents a crucial step in the management of cultural heritage and in regional development. Cultural heritage ownership rests with society which may also decide on the access conditions; in principle, no citizen can be excluded from its use. Clearly, the specific nature of cultural heritage as a collective good also implies that the investment and maintenance costs have to be covered by all citizens. Free ridership is not a meaningful option under such circumstances, so that usually taxation schemes – sometimes accompanied by private transaction schemes (such as entry tickets) or even subsidisation schemes – are put in place to ensure financial viability of maintaining the stock of cultural heritage. Consequently, valuation issues of cultural heritage deserve a prominent place in the socio-economic analysis of these assets. Cultural heritage has another feature which gives it a specific characteristic: it is usually unique in nature and hence not substitutable. Consequently, the social value of cultural heritage cannot be assessed by means of normal market transactions, as the usual conditions for market transactions are lacking. In conclusion, the evaluation of cultural heritage is fraught with many complex problems of both an economic and socio-cultural nature. There is not an unambiguous approach that has a universal validity. Rather, there are classes of assessment and evaluation methods that may be helpful in specific cases. . In the history of evaluation a wide variety of different methods has been developed, such as social cost-benefit analysis, planning balance sheet analysis, community impact assessment, multicriteria analysis, participatory group decision analysis, shadow project evaluation, and so forth. There is not a single best method, as the valuation of non-traded goods cannot be solved in a straightforward manner. The present paper aims to offer a concise introduction to the problems at hand and to discuss various classes of evaluation techniques that have been developed and employed in the past years. Despite the appreciation of the role played by cultural heritage in the development of the city, research efforts have not been sufficiently integrated to tackle the complex issues related to its conservation and the need to develop comprehensive approaches and methodologies for its management. Valuation methods play a strategic role in this context. They represent an essential tool to assess the value of urban heritage per se, the potential economic benefits of its transformation, the damage caused to it by environmental hazards, and the benefits of alternative management options for its exploitation. However, evaluation of cultural heritage cannot be based on generic assessment techniques, but has to be performed by tailor-made methods that address the specifications of cultural assets. This paper discusses a way forward.
Keywords: 330